Left atrial dimensions – Is left atrial volume calculation always necessary? - Leitman, Marina; Vered, Zvi (SA Heart Journal, 2017)
Background: Left atrial size may increase with hypertension, diastolic dysfunction, atrial fi brillation, valvular disease, ischaemic heart disease and heart failure. Accurate measurement of left atrial size is important as it can help in the diagnosis and management of heart diseases. Recently, left atrial volume has been recommended for the accurate measurement of the left atrial size. These measurements are complex and sometimes controversial. In this study we sought to investigate when left atrial volume measurement may not be necessary. Methods: One hundred echocardiographic studies were selected retrospectively according to the left atrial size - diameter and/or left atrial area. Twenty-five patients were included in each of the 4 groups: severe, moderate, mildly dilated and normal left atrium respectively, according to routine 2-dimesional (2D) echo measurements. Then, left atrial size was recalculated and left atrial volume was computed and adjusted to the body size. Results: Initial diagnosis of normal left atrial size and severely dilated left atrium were accurate in 100% of the evaluated studies, according to left atrial diameter and left atrial area. In patients with mild and moderate left atrial dilatation, the left atrial area was usually underestimated. Conclusion: If normal, or severe, left atrial dilatation is found by simple measurements of antero-posterior diameter and area, further calculation of left atrial volume index may not be necessary. In all other cases left atrial volume index should be calculated to accurately grade left atrial dilatation.